Association of oxidative stress, programmed cell death, GSTM1 gene polymorphisms, smoking and the risk of lung carcinogenesis: A two-step Mendelian randomization study - Wang, Yijun; Yang, Qiongling; Zheng, Lingzhen (Frontiers in Physiology, 2023)
Aim We aimed to examine the association of oxidative stress, programmed cell death, smoking, and the GSTM1 gene in the risk of lung carcinogenesis. The two-step Mendelian randomization was used. Methods: In the first step, we examined the effect of exposure to smoking on lung carcinogenesis and programmed cell death. We performed a study on a total of 500, 000 patients of European ancestry, from which we obtained genotype imputation information from 488, 377 patients from the UK Biobank by genotyping two arrays: the UK Biobank Axiom (UKBB), which accounted for 95% of marker content, and the UK , Axiom (UKBL). The association between exposure (smoking) and the outcome (lung carcinogenesis) was unmasked. In the second step, we examined the effect of smoking on oxidative stress,programmed cell death and the incidence of lung carcinogenesis. Results Different outcomes emerged from the two-step Mendelian randomization. The gene variant GSTM1 gene was key to the development of lung carcinogenesis. The deletion or deficiency of the gene induces lung carcinogenesis. The GWAS study in participant information obtained from the UK Biobank reveals that smoking interferes with the GSTM1 gene and causes programmed cell death in the lungs, all of which causes lung carcinogenesis: the relative risk of lung carcinogenesis associated with oxidative stress was (a hazard ratio of 17.8, 95% confidence interval of 12.2 to 26.0) among current smokers and (a hazard ratio of 16.6 and a 95% confidence interval of 13.6 to 20.3) among heavy smokers vis-à-vis individuals who never smoked. The gene GSTM1 polymorphism and found to be 0.006 for the participants who have never smoked, <0.001 for the ever-smokers, and 0.002 and <0.001 for current and former smokers, respectively. Conclusion Exposure to smoking is central to the development of lung carcinogenesis. Exposure to smoking is associated with the mediator, programmed cell death: all of which are associated with lung carcinogenesis. Oxidative stress caused by smoke is also key to the mechanism of lung carcinogenesis. The outcomes of the present study reveal the association between oxidative stress, programmed cell death, and the GSTM1 gene in lung carcinogenesis.